2023
DOI: 10.1302/2046-3758.128.bjr-2022-0449.r1
|View full text |Cite
|
Sign up to set email alerts
|

Adiponectin inhibits fibrosis of the palmar aponeurosis in Dupuytren’s contracture in male patients

Abstract: AimsDupuytren’s contracture is characterized by increased fibrosis of the palmar aponeurosis, with eventual replacement of the surrounding fatty tissue with palmar fascial fibromatosis. We hypothesized that adipocytokines produced by adipose tissue in contact with the palmar aponeurosis might promote fibrosis of the palmar aponeurosis.MethodsWe compared the expression of the adipocytokines adiponectin and leptin in the adipose tissue surrounding the palmar aponeurosis of male patients with Dupuytren’s contract… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(4 citation statements)
references
References 43 publications
0
4
0
Order By: Relevance
“… 41 Adiponectin is decreased in the adipose tissue around the palmar aponeurosis of patients with Dupuytren’s contracture, and it suppresses fibrosis of the palmar aponeurosis in a concentration-dependent manner. 20 The current study showed that the addition of adiponectin to db/db mice fibroblasts in vitro suppressed hyperglycaemia-induced upregulation of fibrosis-related genes, excluding TGF-β1, suggesting that adiponectin improves tissue remodelling; in contrast, metformin alone led to an irreversible effect. Thus, metformin-induced inhibition of fibrosis in the knee joint capsule in vivo might be caused by the combinational effect of TGF-β1 inhibition and adiponectin.…”
Section: Discussionmentioning
confidence: 52%
See 3 more Smart Citations
“… 41 Adiponectin is decreased in the adipose tissue around the palmar aponeurosis of patients with Dupuytren’s contracture, and it suppresses fibrosis of the palmar aponeurosis in a concentration-dependent manner. 20 The current study showed that the addition of adiponectin to db/db mice fibroblasts in vitro suppressed hyperglycaemia-induced upregulation of fibrosis-related genes, excluding TGF-β1, suggesting that adiponectin improves tissue remodelling; in contrast, metformin alone led to an irreversible effect. Thus, metformin-induced inhibition of fibrosis in the knee joint capsule in vivo might be caused by the combinational effect of TGF-β1 inhibition and adiponectin.…”
Section: Discussionmentioning
confidence: 52%
“…Adiponectin is an important adipokine with anti-inflammatory and antioxidant effects that improves remodelling and suppresses fibrosis in various pathological conditions, such as diabetic nephropathy and atrial fibrillation. 18 - 20 Metformin increases adiponectin secretion. 40 In patients with scleroderma and advanced fibrosis, the abundance of adiponectin and its receptor are reduced, suggesting that adiponectin is involved in progressive fibrosis in chronic fibrotic diseases.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations